2017
DOI: 10.1051/0004-6361/201628472
|View full text |Cite
|
Sign up to set email alerts
|

A gas density drop in the inner 6 AU of the transition disk around the Herbig Ae star HD 139614

Abstract: Context. Quantifying the gas surface density inside the dust cavities and gaps of transition disks is important to establish their origin. Aims. We seek to constrain the surface density of warm gas in the inner disk of HD 139614, an accreting 9 Myr Herbig Ae star with a (pre-)transition disk exhibiting a dust gap from 2.3±0.1 to 5.3±0.3 AU. Methods. We observed HD 139614 with ESO/VLT CRIRES and obtained high-resolution (R∼90 000) spectra of CO ro-vibrational emission at 4.7 µm. We derived constraints on the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 122 publications
(204 reference statements)
2
32
0
Order By: Relevance
“…All disks to date that have been sufficiently resolved show gas cavities that are smaller than the dust cavities, an indication of one or more undetected companions (Zhu et al 2011;Pinilla et al 2012;Fung et al 2014). Small gas rings were previously suggested by near-infrared observations of the rovibrational CO lines in some transition disks (Pontoppidan et al 2008;Brown et al 2012;Carmona et al 2017), but ALMA observations allowed the determination of the radial structure of the gas surface density profile through imaging of the rotational CO line, tracing the bulk of the gas, suggesting the clearing by a companion. A consequence of this clearing process is the existence of pressure bumps at the outer gap gas edge, where millimeter dust will be trapped due to gas-dust drag (e.g., Weidenschilling 1977;Zhu et al 2011;Pinilla et al 2012) and show a narrow dust ring or in certain cases asymmetric dust rings due to Rossby-wave instability (Barge & Sommeria 1995;Klahr & Henning 1997) or eccentric planet orbits (Ataiee et al 2013;Ragusa et al 2017).…”
Section: Introductionmentioning
confidence: 92%
“…All disks to date that have been sufficiently resolved show gas cavities that are smaller than the dust cavities, an indication of one or more undetected companions (Zhu et al 2011;Pinilla et al 2012;Fung et al 2014). Small gas rings were previously suggested by near-infrared observations of the rovibrational CO lines in some transition disks (Pontoppidan et al 2008;Brown et al 2012;Carmona et al 2017), but ALMA observations allowed the determination of the radial structure of the gas surface density profile through imaging of the rotational CO line, tracing the bulk of the gas, suggesting the clearing by a companion. A consequence of this clearing process is the existence of pressure bumps at the outer gap gas edge, where millimeter dust will be trapped due to gas-dust drag (e.g., Weidenschilling 1977;Zhu et al 2011;Pinilla et al 2012) and show a narrow dust ring or in certain cases asymmetric dust rings due to Rossby-wave instability (Barge & Sommeria 1995;Klahr & Henning 1997) or eccentric planet orbits (Ataiee et al 2013;Ragusa et al 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Modeling work by Antonellini et al (2016) found that the infrared water spectrum should respond to the formation and size of an inner cavity with a specific spectral signature, where the depletion of hotter to colder gas by increasing the inner cavity size produces a decrease of higher-excitation lines at shorter wavelengths (3-17 µm) to lower-excitation lines at longer wavelengths (25-35 µm), a spectral signature that is observed in the data (Banzatti et al 2017). Thermo-chemical model fits to spectrally-resolved infrared CO emission in Herbig disks estimated the gas column density as a function of inner disk radius, and clarified that when not observed, the CO gas column density must be depleted by at least a few orders of magnitude (Bruderer 2013;Carmona et al 2017;Bosman et al 2019). In some cases, spatiallyresolved imaging has also shown depletion of CO gas inside dust cavities (Pontoppidan et al 2008;van der Marel et al 2016van der Marel et al , 2018.…”
Section: Inner Disk Dust Cavities and The Depletion Of Molecular Gasmentioning
confidence: 57%
“…In addition, narrow-line components (originating in more compact but relatively hot and dense regions, such as hot spots at the stellar surface or in the accretion shock region) would be stronger for the lines with high transition probability because low transition probability lines would be more susceptible to collisional deexcitation in these environments. Such departures from disklike profile related to optical depth are also observed in CO lines (e.g., see Panić et al 2008;Hein Bertelsen et al 2016;Carmona et al 2017), contributing to the box-like appearance of optically thick lines. As in such cases, Fe I lines with various optical depths can give information concerning the vertical temperature structure.…”
Section: Line Ratio Constraints On the Inner Diskmentioning
confidence: 71%